2015
DOI: 10.1016/j.proeng.2015.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Prospect of Moringa Seed Oil as a Sustainable Biodiesel Fuel in Australia: A Review

Abstract: Moringa oleifera is one of the most widely cultivated crops in tropical and sub-tropical areas in the world. The common name is drumstick which contains 6 to10 seeds. The matured seeds yield 38 -40% of colourless and odorless vegetable oil. The oil contains concentrated oleic acid which has the potential to be used as a biodiesel. The study reviewed the prospect of moringa oleifera seed oil as a source of alternative transport fuel in Australia. The distributions, habitat, growth, production, oil extraction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 23 publications
1
37
0
1
Order By: Relevance
“…It can be seen that the results obtained are different for the two biodiesels. The literature reported that biodiesel is a carbon-neutral fuel and the combustion of biodiesel in CI engines emits lower greenhouse gases than fossil diesel [61,62]. The trend shows the decrease in CO2 emission with the increase of biodiesel percentage.…”
Section: Emission Analysismentioning
confidence: 99%
“…It can be seen that the results obtained are different for the two biodiesels. The literature reported that biodiesel is a carbon-neutral fuel and the combustion of biodiesel in CI engines emits lower greenhouse gases than fossil diesel [61,62]. The trend shows the decrease in CO2 emission with the increase of biodiesel percentage.…”
Section: Emission Analysismentioning
confidence: 99%
“…For the renewable energy supply, 6% comes from clean energy (zero emission energy such as solar, wind, hydro, wave, etc.) and 10% from bioenergy (i.e., biomass and biodiesel) [3,4]. Nowadays, greenhouse gas emissions are one of the major concerns throughout the globe because of the increasing evidence of the adverse effects of global warming.…”
Section: Introductionmentioning
confidence: 99%
“…Rahman et al [13], investigated palm oil as one of the vegetable oils widely used as a diesel fuel alternative. Other studies on alternative fuels that investigated the use of coconut [14,15], moringa [16], peanut [17], soybean [18,19], and rapeseed oils generated positive results [20].…”
Section: Introductionmentioning
confidence: 99%